Rural tourism as a driver of the economic and rural development in the Republic of Serbia - Dimitrijević, Miloš; Ristić, Lela; Bošković, Nikola (Hotel and Tourism Management, 2022)
Rural tourism supports the linking of the economic, social and environmental development elements, while boosting employment and stepping up rural development This paper aims to assess the importance of rural tourism in terms of the economic and rural development in the Republic of Serbia. The Kruskal-Wallis test was used to compare the values referring to the number of registered tourist arrivals and overnight stays per region. According to the research findings, the region of Šumadija and Western Serbia has the largest number of rural households and also records the highest number of tourist arrivals and overnight stays. In developed countries, the tourism industry strongly supports the agricultural sector by creating new jobs and contributing to the overall economic development, however, the situation is quite different in Serbia. Furthermore, considering the EU, where the rural areas cover a large part of the overall territory, it is exactly the rural areas that account for a significant number of overnight stays and accommodation facilities.